The Role of Artificial Intelligence in the Learning and Teaching of a Foreign Language - Ranjan, Ritesh (Management Analytics and Social Insights, 2026)
Artificial Intelligence (AI) has significantly transformed the landscape of foreign language learning and teaching. This paper examines how AI tools, such as Intelligent Tutoring Systems (ITS), Natural Language Processing (NLP), and speech recognition technologies, enhance pedagogical practices by offering personalized instruction, real-time feedback, and immersive learning environments. It also investigates the implications of these technologies on learner autonomy, teacher roles, and the challenges posed by over-reliance on automation and cultural contextualization. By evaluating current applications and emerging trends, the study underscores AI's potential to reshape foreign language education and identifies the pedagogical considerations necessary for its effective integration.